1998
DOI: 10.1136/ard.57.11.691
|View full text |Cite
|
Sign up to set email alerts
|

T cell derived cytokines in psoriatic arthritis synovial fluids

Abstract: (Ann Rheum Dis 1998;57:691-693)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
45
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 13 publications
3
45
0
3
Order By: Relevance
“…It has been shown that keratinocytes in psoriatic lesions resist apoptosis and have prolonged survival (12). In addition, IFN-y induces macrophages to release high levels of other inflammatory cytokines including TNF-a which are present at higher levels in psoriatic plaques and in the synovial fluid of patients with psoriatic arthritis (13)(14). The IL-2 receptor, CD25, is up-regulated on T cells within psoriatic lesions (15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that keratinocytes in psoriatic lesions resist apoptosis and have prolonged survival (12). In addition, IFN-y induces macrophages to release high levels of other inflammatory cytokines including TNF-a which are present at higher levels in psoriatic plaques and in the synovial fluid of patients with psoriatic arthritis (13)(14). The IL-2 receptor, CD25, is up-regulated on T cells within psoriatic lesions (15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…This notion is based on the presence of T lymphocytes in early psoriasis lesions (16), the beneficial effects of T lymphocyte-targeted therapies such as cyclosporin A (8), and the altered relationship between psoriatic keratinocytes and interferon-␥ (IFN␥) compared with normal keratinocytes (17). Data on the role of T cells in PsA are limited, but it has been suggested that they play a central role in its pathogenesis as well (18)(19)(20).…”
mentioning
confidence: 99%
“…Considerable evidence implicates T cells in the pathogenesis of psoriatic arthritis as well as psoriasis. This includes the presence of T cells at sites of inflammation, the response of the disease to therapy directed at T cells, and the association of disease susceptibility with certain HLA alleles (1)(2)(3)(4)(5)(6). In particular, the specific importance of CD8 lineage T cells in the pathogenesis of psoriatic arthritis (7) is emphasized by three observations.…”
mentioning
confidence: 99%